Patient’s motivation to participate in psychotherapy - Kulik, Teresa Bernadetta; Bieniarz, Anna; Pacian, Anna; Janiszewska-Grzyb, Mariola (Polish Journal of Public Health, 2009)
Patient’s motivation for starting the therapy is one of the key points considered for qualifying the patient for psychotherapy. Strongly motivated patients get better results Turing pharmacological treatment and also make more Progress in the course of psychotherapy process as compared to not motivated ones. The study is an overview of accessible literature on motivation for starting therapy, mainly psychotherapy In psychiatric patients and in subjects seeking professional help in solving their psychical problems. A special emphasis Has been put to the following aspects: – motivation for getting rid of annoying symptoms – concern about the consequences of psychotherapy or getting help from psychologist or psychotherapist – readiness for learning the causes of disease or mental disorder – external forces for starting therapy – readiness for changes – expecting secondary advantages from the disease – denying of the disease or mental disorder. Also the results of the recent research in this fi eld have been presented. The study discusses the presented results of research.